Burden of schizophrenia on selected comorbidity costs. (April 2014) - Lafeuille, Marie-Hélène; Dean, Jason; Fastenau, John; Panish, Jessica; Olson, William; Markowitz, Michael; Duh, Mei Sheng; Lefebvre, Patrick
<x xml:space="preserve">Abstract</x> Patients suffering from schizophrenia tend to have high rates of medical comorbidities and mortality.This study evaluated the healthcare costs of patients with schizophrenia and specific comorbidities relative to patients without schizophrenia with the same comorbidities, using Medicaid insurance claims databases from five states (from 2001–2010). The most common comorbidities were hypertension (48.8%), substance abuse (39.1%) and diabetes (28.4%). Patients with schizophrenia incurred greater all-cause monthly healthcare costs (cost difference [95% CI]: US978 [933; 1024]) and comorbidity-related costs (cost difference [95% CI]: US288 [269; 307]). Schizophrenia was also associated with significantly higher comorbidity-related costs in each comorbidity subgroup (among the three most common comorbidities: 99% higher in hypertension, 293% in substance abuse, and 105% in diabetes). The results suggest that patients with schizophrenia and comorbidities common in patients with schizophrenia had higher all-cause and comorbidity-related healthcare costs compared with patients without schizophrenia with the same comorbidities.